Dinâmica populacional dos quítons (Mollusca: Polyplacophora) da Praia do Pacheco, Caucaia, Ceará, Nordeste do Brasil - Vasconcelos, Socorro Jeyce Rocha (2011)
Species that live on and under boulders in intertidal areas and fields of boulders are likely to have similar patterns of spatial or temporal. The boulders found in intertidal habitats are complex and naturally ragmented This substrate serves as refuge for crabs and chitons against desiccation and tidal action. The chitons are adapted to live under these boulders and their distribution is affected by several changes that the environment suffers throughout the year. This study aimed to describe the distribution of chitons Praia do Pacheco, Caucaia, Ce. Data were collected monthly from August 2009 until July 2010. Two transects were drawn perpendicular to each other distant beach, about 25 meters. Along the transects were sampled every ten meters, beginning the first point after sixty meters from the top of the sand, and at every point three replicates were made bounded by a square PVC 50 x 50 cm. All the boulders were checked and found each specimen was identified, then its total length was measured as the boulders. We have found only two species, both family Ischnochitonidae: Ischnochiton striolatus and Ischnoplax pectinata. Observed a total of 2107 chitons throughout the study period, of which 1629 were identified as I. striolatus (77.31%) and 478 (22.69%) as I. pectinata. I. striolatus was identified as the most abundant and both species were more abundant in transect 1 (when comparing the two transects) and zone 2 (compared to the two zones). The peak of abundance occurred in August 2009 with the specie I. striolatus. The salinity and rainfall showed a negative correlation with total abundance of chitons. Both species showed a positive correlation between the abundance and size of boulders. The density of I.striolatus ranged between 0.013 and 0.431 ind / m², while the density of I. pectinata ranged between 0.0033 and 0.178 ind/m².In general, the greater is the density of I. striolatus for I. pectinata and both species have higher densities in zone 2, compared with that seen in the area 1.The average size of I. striolatus is 9.70 ± 1.53 mm, while that of I. pectinata ± 3.71 is 12.46 mm and no species has its size influenced by abiotic factors (salinity and rainfall). The frequency distribution of monthly size was unimodal for both species. Positive correlation was found between the size of both species and sizes of boulders inhabited by them.